Diagnostics for detection and surveillance of priority epidemic-prone diseases in Africa: an assessment of testing capacity and laboratory strengthening needs - Ashenafi, Aytenew; Sule, Olajumoke; Peter, Trevor; Mashate, Silver; Otieno, Osborn; Kebede, Abebaw; Oio, John; Kao, Kekeletso; Carter, Jane; Whistler, Toni; Ndlovu, Nqobile; Kebede, Yenew (Frontiers in Public Health, 2024)
The identification and monitoring of priority epidemic-prone diseases in Africa involve various crucial aspects that are vital for enhancing public health interventions and responses. This assessment of testing capabilities and the requirement for strengthening laboratories reveals the existing testing capacity, such as disease-specific diagnostics for viral Hemorrhagic fevers (VHFs) like Ebola, Marburg, and Lassa fever. These diagnostics need advanced biosafety laboratories and specialized molecular diagnostic tools like RT-PCR. Additionally, it highlights the gaps in disease surveillance and response across the African continent.